2009
DOI: 10.1002/ctpp.200910024
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Heterogeneities in 2D Dusty Plasma Liquids at the Discrete Level

Abstract: Down to the discrete microscopic level, the liquid is neither homogeneous nor completely disordered. The interplay of mutual coupling and thermal agitation makes the system support short range structural order, and avalanche-type cooperative hopping excitations which lead to structural arrangement. The rich dynamical behaviors of spatio-temporal heterogeneities are still poorly understood because of the lack of proper tools for direct visualization. The dusty plasma liquid can be self-organized by negatively c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 98 publications
(204 reference statements)
1
13
0
Order By: Relevance
“…Similar to the 2D system, ordered domains with triangular lattice type structures, in which dusts exhibit caged oscillation, are surrounded by disordered regions with defects where dusts exhibit cooperative horizontal hopping and rearrange the microstructure. 14,16,17 Overlapping the dust trajectory plots of the above three different planes shows that the structures and motions for different layers are only similar in some regions ͓Fig. 2͑d͔͒.…”
Section: A Cooperative Chain Excitationsmentioning
confidence: 97%
See 4 more Smart Citations
“…Similar to the 2D system, ordered domains with triangular lattice type structures, in which dusts exhibit caged oscillation, are surrounded by disordered regions with defects where dusts exhibit cooperative horizontal hopping and rearrange the microstructure. 14,16,17 Overlapping the dust trajectory plots of the above three different planes shows that the structures and motions for different layers are only similar in some regions ͓Fig. 2͑d͔͒.…”
Section: A Cooperative Chain Excitationsmentioning
confidence: 97%
“…[14][15][16] Previous studies showed that, in the horizontal ͑xy͒ plane, its structure has many small triangular lattice type ordered domains surrounded by defect clusters, similar to other 2D liquids. [14][15][16][17][18][19][20] The chains exhibit thermal induced stick-slip horizontal motion, with alternating small amplitude oscillation in the caging well formed by the nearest neighbors, and cooperative horizontal hopping over the caging barrier after accumulating sufficient constructive perturbations from thermal kicks and strain induced stress. [14][15][16] The hopping induces defect motion and structural rearrangement.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations